Effects of LiAl-Layered Double Hydroxides on Early Hydration of Calcium Sulphoaluminate Cement Paste - 李海艳;管学茂;YANG Lei;LIU Songhui;ZHANG Jianwu;GUO Yanan (Journal of Wuhan University of Technology. Materials science edition, 2017)
As a 3D micro-nano material, layered double hydroxides have been widely used in many fields, especially for reinforced composite materials. In this paper, Li Al-LDHs was obtained by a hydrothermal method. In order to investigate the effects of Li Al-LDHs on the early hydration of calcium sulphoaluminate（CSA） cement paste, compressive strength, setting time and hydration heat were tested while X-ray diffraction（XRD）, Fourier transform infrared spectroscopy（FT-IR）, scaning electron microscopy（SEM） and differential scanning calorimetry（DSC） analysis were employed. The results indicated that Li Al-LDHs could significantly improve the early compressive strength and shorten the setting time of calcium sulphoaluminate cement paste with 3 wt% concentration. Besides, the hydration exothermic rate within 5h was accelerated with increasing Li Al-LDHs content. Moreover, the addition of Li Al-LDHs did not result in the formation of a new phase, but increased the quantity of hydration products providing higher compressive strength, shorter setting time and denser microstructure.